The Snowflake Heart / Hershey Children’s Hospital / Night Stand - Kuhar, Larry (Ars Medica, 2017)
These three poems contemplate, in different ways, circumstances and experiences related to a diagnosis of congenital heart disease and the related trip to the Hershey Children's Hospital in Hershey, PA.